Geoelectrical soundings in the Combeynot Massif (French Alps) : Characterisation of Alpine permafrost and geodynamics of the Southern Alps . - Bodin, Xavier; Fabre, D.; Ribolini, Adriano; Schoeneich, Philippe; Fort, Monique (HAL CCSD, 2007)
Abstract volume p. 19. International audience